CHANGES IN IMMUNOLOGICAL INDICATORS IN CHILDREN WITH CHRONIC VIRAL HEPATITIS B (Journal of Universal Science Research, 2023)
Hepatitis B can be transmitted only through contact with biological materials of the patient. In many cases, the infection goes unnoticed by the patient, so the disease is detected as a result of laboratory analyzes or when characteristic symptoms appear. People who are treated in time will recover completely from hepatitis B disease and will form stable immunity against this disease.